Balancing tension in transferred slips in some dynamic procedures for claw finger correction - Malaviya G (Indian Journal of Plastic Surgery)
The adjustment of tension on the tendon slips which are being inserted to correct finger clawing, is the critical step in claw finger correction procedures. Several methods have been described in literature but ultimately every thing boils down to the experience of the operating surgeon who has to make decisions on the operating table. Attempt is being made to translate this experience (an abstract noun) in to words to help make life easier for the surgeons who are venturing into the field of corrective surgery and do not have enough experience to back them.